Predictors of infant-survival practices among mothers attending paediatric clinics in Ijebu-Ode, Ogun State, Nigeria - Eniolufolake Elizabeth Sokefun; Nnodimele Onuigbo Atulomah (BMC, 2020)
Abstract Background Despite concerted global efforts towards achieving infant-survival, infant mortality lingers as a problem in developing countries. Environmental and personal-level factors are assumed to account for this situation. This study was undertaken to provide better understanding of the dynamics of predictors of infant-survival practices among mothers with infants attending paediatric clinics. Methods A cross-sectional survey design was adopted. Data was collected from 386 nursing mothers selected by convenience sampling. Interviewer-administered questionnaires were used for data collection. The questionnaire consisted of 38-items including demographic information of respondents, health-literacy counsels received during antenatal care, social-support from significant others, and self-efficacy to carry-out infant-survival instructions. Responses were transformed into rating scales for each variable and data analysis was conducted by linear regression analysis with test of hypotheses at 5% level of significance. Results The mean age of respondents was 29.8 ± 5.8 years. Majority (81.6%) were married. Yorubas (83.90%) were predominant. Participants had mean scores of 10.50 ± 3.83, 10.56 ± 3.70 and 16.61 ± 4.56 respectively computed for levels of health-literacy, social-support, and self-efficacy. The dependent variable measured level of infant-survival practices and respondents scored 16.53 ± 4.71. The study found a significant association among variables. Self-efficacy was the major predictor variable of self-reported infant-survival practices (R = 0.466; R2 = 0.217; P<0.05). Conclusion We conclude that participants had average levels of health-literacy, social-support, self-efficacy, and infant-survival practices. Healthcare providers should make efforts to empower pregnant women on activities essential for infant-survival. Family members of nursing mothers should as well be knowledgeable about the advantages of supporting them.